THE ROLE OF PRINCIPAL LEADERSHIP IN BUILDING AN INCLUSIVE SCHOOL CULTURE TO SUPPORT SOCIAL ROOM EDUCATION - Yosep Heristyo Endro Baruno; Juliana Loes; Yosua Padama (Indonesian Journal of Education (INJOE), 2025)
The principal's leadership plays an important role in building an inclusive school culture to support social space-based education. Inclusive education emphasizes equal access, active participation, and an environment that supports student diversity. This literature review aims to analyze how principal leadership can create an inclusive school culture that encourages healthy social interactions and improves student well- being. This research uses a literature review approach with descriptive- qualitative methods to analyze inclusive educational leadership theories and best practices that have been implemented in various schools. The findings show that school principals who have an inclusive vision are able to implement strategic policies, build effective communication, and collaborate with various parties to create a friendly learning environment for all students. Case studies from various countries also reveal that a social booth-based approach can increase student engagement, reduce discrimination, and strengthen the values of tolerance in school communities. The implications of this research emphasize the importance of educational policies that support inclusive leadership training for school principals as well as strengthening regulations related to inclusive schools. In addition, school principals need to adopt a transformative and collaborative leadership model to ensure that an inclusive culture can be implemented sustainably. With the right strategy, schools can become spaces that not only provide academic education, but also shape the social character of students who are more empathetic, tolerant and ready to face life in a diverse society.